Term Limit Extension and Electoral Participation: Evidence from a Diff-in-Discontinuities Design at the Local Level in Italy - Marco Alberto De Benedetto; Maria De Paola (Institute of Labor Economics (IZA), 2018)
We study the effect of term limits on voter turnout in local Italian elections. Since 2014 the Italian law allows mayors in municipalities with a population size lower than 3,000 inhabitants to re-run for a third term, whereas mayors in cities with a number of residents above the cutoff still face a two-term limit. The introduction of the reform permits us to implement a difference-in-discontinuities design exploiting the before/after with the discontinuous policy change. We find that voters negatively react to the introduction of the reform and in particular electoral participation decreases by about 5 percentage points in municipalities eligible to the treatment compared to municipalities in the control group. This negative effect is essentially driven by a decrease in the political competition. We also find that relaxing term limits does not improve the quality of politicians running for election.
Keywords: C21; D72; H70; J78; 330; diff-in-discontinuities; voter turnout; political competition